Dampak Pelatihan Pengembangan, Motivasi Kerja, dan Perilaku Organisasi Terhadap Prestasi Kerja Pada Dinas Lingkungan Hidup Surakarta - Restu Putri Permatasari; Agus Suyatno; Khabib Alia Akhmad (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
Study This aim for know influence training and development, motivation work, and behavior organization to performance Work Environmental Service employes Long live the city of Surakarta. Study This use method study quantitative. Population in study is Environmental Service employees Live the working city of Surakarta more of 1 (one) year and amount sample in study This as many as 60 respondents use technique purposive sampling. Variables used​ in study This is training and development, motivation work, behavior organization, and achievement Work employee. Data used in research in the form of primary data. Method data collection used is questionnaire. Research result This pointed out that training and development influential positive and significant to performance Work employees, motivation Work influential positive and significant to performance Work employees, behavior organization influential positive and significant to performance Work employees, as well training and development, motivation work, and behavior organization in a way simultaneous (together) influence to performance Work employee.